The importance of contracts in Islamic transactions / Nurfarzana Huda Shahanand … [et al.] - Shahanand, Nurfarzana Huda; Zamri, Muhammad Faiz Iqmal; Osman, Nur Iylia' Syamimi; Baharudin, Anis Masithah; Affandy, Nazirah (2023)
Contract law, being a very special branch of law, stands in the hub of business activities in such a pertinent way that enhances business transactions not only at the national level but also at the international level as well. Corporations are performing million-dollar business transactions and numerous business contract documents are signed on behalf of the company with the pure intention of making a legitimate profit for the company shareholders. (Jalil, 2010). The philosophy of law in Islam differs from the Western philosophy of law quite significantly. The Islamic philosophy says this world was created by only one God known as 'Allah' and all materials on earth and in the universe were created by Him and He alone managed this creation. There were angels to help him but without the help of angels, He was just as capable of accomplishing this monumental task without any problem in whatever way He wished and planned. The Islamic religion emphasizes the importance of the law of contract. The Islamic law of contract has detailed provisions to ensure viable business transactions between companies. Islam only prohibits earnings through usury or interest in business as clearly mentioned in the Al-Quran. Allah (God) says in the holy Quran: 'Taking interest on the loan is prohibited for you but doing business is permitted for you'.